Heterologous expression and characterization of a thermoalkaliphilic SAM-synthetase from giant leucaena (Leucaena leucocephala subsp glabrata) - Carrillo, James T (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 The Authors. Published by Elsevier Masson SAS.. All rights reserved.